# Can someone please help me?$15660x2/3x1/2=5220.($15660-5220)x2/3=6960.I have this part figured out, but I need an answer to the next part.($15660-answer)x2/3=answer. ($15660-answer)-600=answer.I...

Can someone please help me?

$15660x2/3x1/2=5220.

($15660-5220)x2/3=6960.

I have this part figured out, but I need an answer to the next part.

($15660-answer)x2/3=answer.

($15660-answer)-600=answer.

I need this part figured out, because I got the first part figured out.

### 1 Answer | Add Yours

Your question is quite vague as there can be several answers and they all would be right.

We are given the equation: ($15660 -5220) x 2/3 = 6960

Let's use this to determine: ($15660 - answer) – 600 = answer

Now ($15660-5220) x 2/3 = 6960

=> ($15660 - 5220) = 6960 x (3/2)

=> ($15660 - 5220) = 10440

=> ($15660 - 5220) - 600 = 10440 - 600

=> ($15660 - 5220) - 600 = 9840

**Therefore we get ($15660 - 5220) - 600 = 9840**